Polypharmacy and Polytherapy: Current Perspectives on Risk–Benefit Balance and Strategies for Optimization of Multidrug Treatment in Patients - Sozańska, Agata; Nogły, Julia; Mierzwińska-Mucha, Julia; Roś, Bartosz; Siekaniec, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction ​Thanks to the current state of medical knowledge and established clinical guidelines, healthcare professionals can provide patients with comprehensive pharmacotherapy. This is particularly important for individuals with multimorbidity or those for whom monotherapy is insufficient to achieve the desired therapeutic outcomes. However, it is essential to recognize that polypharmacy can pose significant risks to patient safety, especially when care is provided by multiple healthcare providers. Therefore, it is crucial to distinguish rational polypharmacy from inappropriate and undesirable practices, and to be able to identify and avoid adverse effects associated with poorly managed pharmacotherapy and harmful drug interactions.